Adverse Immunologically Mediated Oral Mucosal Reactions to Systemic Medication: Lichenoid Tissue Reaction/Interface Dermatitis-Stomatitis, Autoimmune Vesiculobullous Disease, and IgE-Dependent and Immune Complex Reactions - R. A. G. Khammissa; R. Chandran; A. Masilana; J. Lemmer; L. Feller (Journal of Immunology Research)
Drug-induced hypersensitivity immune reactions are exaggerated immunoinflammatory responses to allergenic components of the medications that occur in genetically susceptible subjects. The type of hypersensitivity immune response generated, whether antibody mediated or T cell mediated, or an immune complex reaction is determined by multiple factors, including the molecular characteristics of the allergen, the route of administration of the medication, the manner of presentation of the allergen by antigen-presenting cells to naïve T cells, the repertoire of the T cell receptors, and the cytokine profile within the microenvironment. This review deals with the clinical and histopathological aspects of adverse immunologically mediated oral mucosal reactions to systemic medication. We elaborate on diseases showing features of lichenoid tissue reaction/interface dermatitis-stomatitis, autoimmune vesiculobullous oral lesions, and immunoglobulin E- (IgE-) and immune complex-mediated oral reactions to drugs.